JAROSITES AND THEIR APPLICATION IN HYDROMETALLURGY - Dutrizac J.E.; Jambor J.L. (My University, 2000)
The alunite supergroup consists of more than 40 minerals with the general formula DG 3( T O4)2(OH,H2O)6, wherein D represents cations with a coordination number greater or equal to 9, and G and T represent sites with octahedral and tetrahedral coordination, respectively (Smith et al. 1998). The supergroup is commonly subdivided into various groups, but the simplest primary subdivision is on the basis of the G cations. For all of the minerals in the supergroup, the dominant G cation is trivalent; most of the minerals have G represented by Fe3+ or Al3+, but exceptions are the rare minerals gallobeudantite, in which G is Ga3+, and springcreekite, in which G is V3+ (Table 1⇓). Thus, the primary grouping adopted here is on whether formula Fe3+ exceeds or is subordinate to Al3+. The hierarchical sequence in mineralogy seems to be variable, but here the decreasing sequence is given as supergroup, family, group, and subgroup. Minerals with Fe3+ > Al3+ are referred to as belonging to the jarosite family, and those with A13+ > Fe3+ are allocated to the alunite family. View this table: Table 1. Minerals of the alunite supergroup. Subdivision of the alunite and jarosite families has also been variable; Scott (1987), for example, used seven groups, Novak et al. (1994) used six, Gaines et al. (1997) used four, and Mandarino (1999) used three. The arbitrary decision here is to use three groups, which differ from those of Mandarino (1999) but which, in general, indicate whether sulfate, phosphate, or arsenate predominates in the T O4 tetrahedra. The three groups are the alunite group, in which T O4 is dominated by SO4, the crandallite group, in which (PO4) is …